An evaluation of the occupational accidents among logging workers within the boundaries of Trabzon Forestry Directorate, Turkey - Enez, Korhan; Topbas, Murat; Acar, Hafiz Hulusi (Elsevier BV, 2014)
Abstract The aim of this study was to determine the frequency of occupational accidents among logging workers and the risk factors involved. Data for 378 out of 2994 members of 24 cooperatives engaged in logging in the study area were gathered using face-to-face questionnaires and anthropometric data via the free measurement method. The annual logging accident frequency rate was 30.4%, and the annual incidence of occupational accidents was 2052.9. The accident risk among workers using hookaroons was 2.14 times greater than the risk among those not using them. Five to six rest breaks a day increased the accident frequency rate by 0.37 times. The foot width, which was one of the variables among the measured anthropometric data, was observed to increase the accident risk 0.68 times. The likelihood of an employee suffering from an accident during the working year correlated with the handling of chainsaws, the use of hookaroons, smoking, the number of breaks taken while working, experience, shoulder and knee height, leg and arm length and hand and foot width. Relevance to industry Even though Turkey is one of the countries in which occupational accidents are frequent, studies or records concerning occupational accidents involving logging workers are currently lacking in Turkey. In this study, the occupational accidents in the forest-wood industry were analyzed, and the methodology for obtaining the data in this industry was described. The results emphasize the magnitude of occupational accidents in forestry in Turkey.
Keywords: 8. Economic growth; 15. Life on land